Isolation, Identification, and Evaluation of the Pathogenicity of a Porcine Enterovirus G Isolated From China - Mi, Xue; Yang, Chunjie; Lu, Ying; Wang, Hejie; Qin, Qiuying; Chen, Ronglin; Chen, Zhenkong; Luo, Yunyan; Chen, Ying; Wei, Zuzhang; Huang, Weijian; Ouyang, Kang (Frontiers in Veterinary Science, 2021)
Enterovirus G (EV-G) infects porcine populations worldwide and the infections are generally asymptomatic, with the insertion of the papain-like cysteine protease gene (PLCP) increasing the potential public health threats. However, the genetic and pathogenic characteristics of EV-G itself are not fully understood as yet. In the present study, one EV-G strain, named CH/17GXQZ/2017, was isolated and purified from piglets with diarrheic symptoms from the Guangxi Province, China. This strain produced stable cytopathic effects on Marc-145 cells with a titer of 5×106 PFU/mL. The spherical enterovirus particles with diameters of 25 ~ 30 nm were observed by using transmission electron microscopy. The whole genome sequence of the CH/17GXQZ/2017 strain consists of 7,364 nucleotides, and the phylogenetic tree based on the amino acid sequences of VP1 indicated this strain was clustered to the G1 genotype. Seven-day-old piglets were inoculated orally with the CH/17GXQZ/2017 strain in order to evaluate its pathogenicity. Although none of the infected piglets died during the experiment, clinical neurological symptoms were observed manifesting as mild hyperemia and Nissl bodies vacuolization in the cerebrum. In addition, the infection with the CH/17GXQZ/2017 strain decelerated the weight gain of suckling piglets significantly. This study demonstrates that CH/17GXQZ/2017 is pathogenic to neonatal piglets and advance knowledge on the biological characteristics, evolution and pathogenicity of EV-G.